O comércio internacional de resíduos rerigosos entre países OCDE e não OCDE: uma análise empírica com destaque para o Brasil - Maia, Thiago Luis Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The transboundary movement of hazardous waste between industrialized countries and developing countries is a controversial subject that has gained greater prominence from the late 80s and early 90s, when as a result of discussions on the illegal trafficking of hazardous toxic waste to countries in development, created the Basel Convention on the Control of Transboundary Movements of Hazardous Wastes and their Disposal. According to the rules of the Basel Convention, the most industrialized countries in the world - belonging to the Organization for Economic Cooperation and Development (OECD) - and developing non-OECD countries can sell hazardous waste provided they meet the requirements of notifications and previous between the Parties involved, combined with a risk management environmentally sound hazardous waste consents. However, the conditions set by the agreement of the Basel Convention were not sufficient to prevent the continuation of illegal trafficking. In subsequent meetings of the Parties to the Convention, it was decided to prohibit the movement of hazardous waste between OECD and non-OECD countries through an amendment to the Basel Convention that has still not been ratified. Although the amendment is not in force, countries may also prohibit trade of hazardous waste through their national legislation if they are interested - as recently did in Brazil with the National Solid Waste that banned the import of hazardous waste. On the other hand, if the ban amendment is approved in the future, institutionally weaker countries receive greater protection from this kind of trade. This dissertation investigates the trade in hazardous waste between OECD and non-OECD countries between 2000 and 2010, highlighting Brazil's insertion in the regulatory framework of the National Solid Waste Policy and the Basel Convention, seeking to test the hypothesis that OECD countries send hazardous waste to non-OECD countries, and also if the ...

O movimento transfronteiriço de resíduos perigosos entre países industrializados e países em desenvolvimento é um assunto controverso que ganhou maior destaque entre o final da década de 80 e o início dos anos 90, quando em consequência das discussões sobre o tráfico ilegal de resíduos tóxicos perigosos para países em desenvolvimento, criou-se a Convenção de Basileia sobre o Controle do Movimento Transfronteiriço de Resíduos Perigosos e seu Depósito Final. De acordo com as normas da Convenção de Basileia, os países mais industrializados do mundo - pertencentes à Organização para a Cooperação e Desenvolvimento Econômico (OCDE) - e os países em desenvolvimento não pertencentes à OCDE poderiam comercializar resíduos perigosos desde que cumprissem as exigências de notificações e consentimentos prévios entre as Partes envolvidas, combinadas a um gerenciamento de riscos de resíduos perigoso ambientalmente adequado. Entretanto, as condições dispostas pelo acordo da Convenção de Basileia não foram suficientes para evitar a continuação do tráfico ilegal. Em encontros posteriores das Partes signatárias da Convenção, decidiu-se proibir o movimento de resíduos perigosos entre países OCDE e não OCDE por meio de uma emenda à Convenção de Basileia, que até hoje não foi ratificada. Apesar desta emenda não estar em vigor, os países também podem proibir o comércio de resíduos perigosos através de suas legislações nacionais caso sejam interessados - como recentemente fez o Brasil com a Política Nacional de Resíduos Sólidos (PNRS), que proibiu a importação de resíduos perigosos. Por outro lado, caso a emenda de proibição seja aprovada no futuro, os países institucionalmente mais fragilizados receberão maior proteção contra esse tipo de comércio. Nesta dissertação, investiga-se o comércio de resíduos perigosos entre países OCDE e não OCDE entre 2000 e 2010, com destaque para a ...
Keywords: Economia; Resíduos perigosos; Resíduos industriais; Desenvolvimento sustentável; Comércio internacional; Economics